Contaminated sites from the past: experience of the US Environmental Protection Agency. (June 2016) - Boyd, M.A.
The purpose of this paper is to provide an overview of the experience of the US Environmental Protection Agency (EPA) in cleaning up radioactively contaminated sites. In the USA, EPA regulates the radiological clean-up of uranium mill tailings sites, some Department of Energy legacy sites within the US nuclear weapons complex, and Superfund National Priorities List sites. The approach to site remediation decisions, including the determination of clean-up levels, varies according to the enabling legislation granting EPA these authorities. Past practices that gave rise to many of the existing exposure situations at legacy sites were permissible before the advent of environmental clean-up legislation. The Uranium Mill Tailings Radiation Control Act of 1978 authorised EPA to set applicable radioactivity concentration standards for soil clean-up at inactive uranium mill sites and vicinity properties. For the other categories of sites mentioned above, remediation goals are typically based on not exceeding a target excess cancer risk range established under the Comprehensive Environmental Response, Compensation, and Liability Act (also known as 'Superfund'). EPA's regulations for cleaning up various contaminated sites in existing exposure situations often result in residual doses that are typical of optimised doses in planned exposure situations. Although the clean-up levels selected may differ from those adopted in other countries, recommendations from the International Commission on Radiological Protection are reflected in the exposure assessment methodologies used in their establishment.